Introduction - Jean Le Dû; Yves Le Berre (La Bretagne Linguistique, 1998)
Presentation of the colloquium "Is there a French sociolinguistic exception?" which took place in Brest on 5, 6 and 7 June 1997, followed by a letter from Renée Balibar.